Novice English Teachers’ Teaching Anxiety: An Exploration Of Its Causes And Coping Strategies - Cindi Tiara Utami (Fakultas Keguruan Dan Ilmu Pendidikan, 2026)
Novice teachers are referred to as new beginners, newly qualified neophytes, and early career teachers in their teaching careers' early years, typically within their first three to five years of teaching (Ingersoll & Strong, 2011). Kelchtermans and Ballet (2002) also claimed that novice teachers are still in the process of developing their professional identities and some some of them experience anxiety in teaching. The issue of teaching anxiety among English teachers has become a growing concern, particularly for novice teachers who are still adjusting to their roles in the classroom. Teaching anxiety can interfere with teachers’ ability to work effectively, especially in an English as a Foreign Language (EFL) environment where English must be actively used in class. This study aims to explore novice English language teachers’ personal experiences in overcoming teaching anxiety during the early stages of their careers. The study focuses on understanding the causes of anxiety and the strategies used to manage it. Several previous studies have examined teaching among pre-service teachers but limited attention has been paid to in-service novice teachers. Therefore, this study seeks to complement this by investigating the experiences of novice EFL teachers who are already involved in real classroom teaching. The study was conducted in a high school in Jember, East Java, with two EFL teachers who had less than five years of teaching experience. The study used a descriptive qualitative design to explore the in-depth experiences of these participants. Followed by a semi-structured interview as a data collection method, the interview was conducted in Indonesian and transcribed verbatim. Data were then analysed using thematic analysis, following Braun and Clarke’s six-step model. The findings of this research highlight several causes of teaching anxiety, such as differences in students’ learning abilities and proficiency levels, lack of confidence, challenges in managing large classes, and difficulty communicating with students. Despite these challenges, participants reported that they used a variety of coping strategies to cope with teaching anxiety. These strategies included seeking support from fellow teachers and institutions through in-house training and peer discussions, which is very importance of institutional support, collaboration with colleagues, and adaptive teaching strategies in helping beginning teachers cope with their anxiety, then having an alternate or back-up lesson plan to manage the unpredictability events during teaching, and using digital resources to support their classroom performance. This study contributes to a deeper understanding of how teaching anxiety manifests among beginning teachers in service and offers practical insights for teacher education programs and school leaders.
Reupload file repositori 21 Mei 2026_Maya Validasi dan Finalisasi Repositori File 11 Juni 2026_Kholif Basri
Keywords: Teaching Anxiety